(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the specific features of civil society development in Uzbekistan under globalization conditions. The research focuses on the formation of civil society institutions, development trends, and prospects. The paper examines modern directions and challenges of civil society development based on national and international experience, with particular emphasis on Uzbekistan's unique path of democratic transformation.